2018
DOI: 10.1017/s1352465818000498
|View full text |Cite
|
Sign up to set email alerts
|

Translating the Intention to Seek Treatment into Action: Does Symptom Monitoring Make a Difference? Results from a Randomized Controlled Trial

Abstract: Symptom monitoring can increase actual treatment-seeking in those with an intention to seek treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Self-monitoring of depressive symptoms on patients' phones has been shown to be easy and reliable [51,52] and several studies highlighted its effectiveness to improve depressive symptoms [36,53,54]. A study on untreated patients with symptoms of depression and anxiety also showed that access to daily self-monitoring helped them to translate their intention to seek treatment into actual treatment-seeking behaviour [55]. Even if this effect was small, it defines self-monitoring as a promising tool to decrease the number of untreated patients suffering from depression.…”
Section: Discussionmentioning
confidence: 99%
“…Self-monitoring of depressive symptoms on patients' phones has been shown to be easy and reliable [51,52] and several studies highlighted its effectiveness to improve depressive symptoms [36,53,54]. A study on untreated patients with symptoms of depression and anxiety also showed that access to daily self-monitoring helped them to translate their intention to seek treatment into actual treatment-seeking behaviour [55]. Even if this effect was small, it defines self-monitoring as a promising tool to decrease the number of untreated patients suffering from depression.…”
Section: Discussionmentioning
confidence: 99%
“…Symptom monitoring has benefited numerous clinical populations, including patients with fibromyalgia, clinical depression, and cancer (3)(4)(5). Symptom monitoring involves recording symptoms using diaries, symptom questionnaires, or electronic health (e-health) instruments, including mobile apps or online symptom trackers; this can take place across time, or retrospectively at one or more given time points (6).…”
Section: Introductionmentioning
confidence: 99%
“…Symptom monitoring involves recording symptoms using diaries, symptom questionnaires, or electronic health (e-health) instruments, including mobile apps or online symptom trackers; this can take place across time, or retrospectively at one or more given time points ( 6 ). Notable outcomes have included increased likelihood of accessing healthcare, heightened survival rates, and reductions in symptom prevalence and severity ( 3 5 , 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, upon the increased intention to use those apps, patients need to learn effective coping strategies and skills to perform and maintain the actual behavior without using excessive reassurance-seeking and relying on safety behaviors. Shafran et al highlighted the importance of daily self-monitoring through, for example, digital trainings in supporting patients with reduced mental health status in translating intentions into actual behavior [69].…”
Section: Xsl • Fomentioning
confidence: 99%